Comparison of the effectiveness four years after Homo/Hetero prime-boost with 10 μg HP and 20 μg CHO recombinant hepatitis B vaccine at 1 and 6 months in maternal HBsAg-negative children - Yin, Zhiying; Wen, Tingcui; Fu, Canya; Li, Junji; Fang, Quanjun; Gong, Xiaoying; You, Jialing; Wang, Shuangqing; Zheng, Canjie (Frontiers in Immunology, 2024)
Limited data were available on the effectiveness four years after Homo or Hetero prime-boost with 10 μg Hansenula polymorpha recombinant hepatitis B vaccine (HepB-HP) and 20 μg Chinese hamster ovary cell HepB (HepB-CHO). A cross-sectional study was performed in maternal hepatitis B surface antigen (HBsAg)-negative children who received one dose of 10 μg HepB-HP at birth, Homo or Hetero prime-boost with 10 μg HepB-HP and 20 μg HepB-CHO at 1 and 6 months. HBsAg and hepatitis B surface antibody (anti-HBs) four years after immunization were quantitatively detected by a chemiluminescent microparticle immunoassay (CMIA). A total of 359 children were included; 119 children received two doses of 10 μg HepB-HP and 120 children received two doses of 20 μg HepB-CHO, called Homo prime-boost; 120 children received Hetero prime-boost with 10 μg HepB-HP and 20 μg HepB-CHO. All children were HBsAg negative. The geometric mean concentration (GMC) and overall seropositivity rate (SPR) of anti-HBs were 59.47 (95%CI: 49.00 – 72.16) mIU/ml and 85.51% (307/359). Nearly 15% of the study subjects had an anti-HBs concentration < 10 mIU/ml and 5.01% had an anti-HBs concentration ≤ 2.5 mIU/ml. The GMC of the 20 μg CHO Homo prime-boost group [76.05 (95%CI: 54.97 – 105.19) mIU/ml] was higher than that of the 10 μg HP Homo group [45.86 (95%CI: 31.94 – 65.84) mIU/ml] (p = 0.035). The GMCs of the Hetero prime-boost groups (10 μg HP-20 μg CHO and 20 μg CHO-10 μg HP) were 75.86 (95%CI: 48.98 – 107.15) mIU/ml and 43.65 (95%CI: 27.54 – 69.18) mIU/ml, respectively (p = 0.041). After controlling for sex influence, the SPR of the 20 μg CHO Homo prime-boost group was 2. 087 times than that of the 10 μg HP Homo group. The HepB booster was not necessary in the general children, Homo/Hetero prime-boost with 20 μg HepB-CHO would increase the anti-HBs concentration four years after immunization, timely testing and improved knowledge about the self-pay vaccine would be good for controlling hepatitis B.